Broiler production efficiency: An analysis using thermal infrared images - Franco, Eldelita; Nääs, Irenilza de Alencar (Revista Brasileira de Engenharia de Biossistemas, 2022)
The study objective was to evaluate the efficiency of using technology focusing on the thermal comfort of broilers in two poultry houses located in the metropolitan region of Teresina, Northeast Brazil, with different technological levels. One level uses cooling control of the housing and adopts high management of good production practices (Tech 1), while the second (Tech 2) was considered to use deficient technology during production. We analyzed the birds’ surface temperature and the environment using infrared surface temperature data. Data were collected at a mean distance of 1 m from the birds using an infrared camera to construct the thermograms on the targets (broilers and surroundings). Data were processed using thermograms, and Boxplot graphs were built. It was found that broilers housed on the farm with higher environmental control (Tech1) obtained a better feed conversion and had more significant weight gain and greater profitability. This indicates that the greater the investment to mitigate heat stress, the better the producer’s economic performance in this activity.